#### Answer

2y - 13

#### Work Step by Step

- (y+1) + 3y - 12 =
(-1 $\times$ y) + (-1 $\times$ 1) + 3y - 12 =
-y -1 + 3y - 12 =
2y - 13

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

2y - 13

- (y+1) + 3y - 12 =
(-1 $\times$ y) + (-1 $\times$ 1) + 3y - 12 =
-y -1 + 3y - 12 =
2y - 13

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.